Compilation of laboratory reports in experimental psychology - Araceli Marie M. De Guzman. 4 0 16; 5 (2017)
Laboratory Report Experiment No.1 SIMPLE REACTION TIME. -----ABSTRACT----- Reflexes require detection, relay, and response. The amount of time it takes for the responseto happen after stimulus is given is identified as the reaction time. in line with this, the researcher conducted an experiment about simple reaction time. The goal o0f the said experiment is to determine if there is an underlying difference in the speed reaction between the two-part-trials taken by the subject test with free association and without free association required. the variables included in this experiment were (1) free association ehich is considered as the stimulus and independent variables (2) reaction time which is considered as the dependent variable. in the first part of the experimentation, the subject held thye timer without looking at it while the experimenter gave a go signal to start the free association with estimations of 12 second interval. The second part did not involve any free association and the subject was able to look at the timer to stop it with the same time interval. The subject performed forty five trials and the data was recorded by the experimenter. After that the experimenter and the subject changed roles and performed only ten trials for the second subject. The hypotheses and results were similar in these ways (1) with free association involved the subject with forty five trials has more tendency to miss the 12 second time target than the second subject with only ten trials (2) without the free association required the subject has more tendency to hit the 12 second time target..;Laboratory Report Experiment No.2 EXTRA SENSORY PHENOMENA.-----ABSTRACT----- Extrasensory means a set of faculties which can perceive events without the use of the basic senses. Many researchers showed interest in proving one's ESP Extra Sensory Perception or ESP includes reception of information not gained through the recognized physical senses but sensed with the mind. The term ESP was popularized by Joseph Banks Rhine who conducted the first laboratory experiment in determining one's ESP using Zener cards. The main objective of this experimentation is to measure the ESP ability under laboratory setting and to determine whether it is possible to attain information without the use of any of the normal senses. The experimenter used a deck of fifty Zener cards with ten cards of each design and recorded the subjects guesses. The subject was given five trials to guess the card design. The experimenter and the subject switched roles to conduct and follow the same procedure. The results however, widely vary and yet were all distinguished as Chance Expectation the effort to establish ESP as a scientific fact has been a continuous struggle the outcome of which still remains uncertain.;Laboratory Report Experiment No.3 OPERANT CONDITIONING. ----- ABSTRACT----- The major theorists for the development of operant conditioning are Edawrad Thorndike , John Watson, and B.F. Skinner. This approach to behaviorism played a major role in the development of the science of psychology, especially in the United Staets. These behaviorists proposed that learning is the result of the applications of consequences that the learners begin to connect certain responses with certain stimuli. This connection causes the likelihood of the response to change whereas learning occurs operant conditioning also referred to as instrumental conditioning is a method of learning that occurs through rewards and punishments for behavior. The goal of the experimentation is to illustrate behavior modification through the application of operant conditioning techniques. There were two experimenters and two subjects. The first subject served as the experimental subject while the second subject was considered as the controlled subject. The experimenters stressed to the subjects that the speed of performance was important. The experimental subject was given verbal reinforcement by the experimenters while the controlled subject did not received any reinforcement. results indicated that there was a substantial relationship between behavior modification and the process of operant conditioning.;Laboratory Report Experiment No.4 FORMATION OF WORD ASSOCIATION AND PERCEPTUAL DEFENSE. ----- ABSTRACT ----- This experimentation was popularized by Sir Francis Carl Jung the formation of word association and perceptual defense aim to measure signs of emotional complexes and to be able to identify the degree of threshold for each selected stimulus, The materials needed were tally sheet, pen, cellphone, stopwatch timer, and ninety nine (99) stimulus word. There were two subjects who performed the experiment each subject has one recorder, time stopper and experimenter. for the procedure, the experiment has two phase 1) determination of association reaction time and 2) the measurement of the recognition thresholds. Ninety nine words were presented one at a time. For the second part of the experiment, the subjects returned after one week and only fifteen (150 selected stimulus words from the first part of the experiment which encompassed three (3) sets of five (5) words that yield the fastest, midmost and slowest association reaction times were presented to the subject with an increased exposure time until the subject recognized the stimulus words correctly. All of the responses were recorded preceding the correct recognition. The Experiment conclude that there were different signs of emotional complexes and different degree of threshold for each selected stimulus words. For the reason that the subject had difficulty in reacting to certain stimulus words the subject felt awkward with some of the stimulus words which made the reaction time slower, thus, the contribution of perceptual defense.;Laboratory Report Experiment No.5 CREATIVITY. ----- ABSTRACT ----- Theories of creativity have focused on a variety of aspects. this experimentation about creativity was performed to measured flexibility, novelty, and originality thru response production of a series of letters. The materials used were stopwatch and anagrams. The procedure was divided into to parts the first part in which the nine anagrams were in jumbled formation and the subject listed as many words as possible. The procedure in the second part was the same in the first part except that the anagrams were already in organized from. The result showed that the first part experiment was easily responded and answered by the subject than in the second part of the experiment. The experiment conclude that the creativity and flexibility could flourished even the circumstances were disorganized such as the response production in the series of letters.;Laboratory Report Experiment No.6 EXPERIMENTATION ON CUTANEOUS SENSITIVITY. ----- ABSTRACT ------ Cutaneous sensitivity was explained by various proponents and famous physiologists. this experimentation was performed to determine various points of adaptation based on different cutaneous sensitivities. the materials used were test tube, ice cubes, hot water, compass and ruler, cork with horsehair, and big handkerchief. The procedure were divided into four parts for the cutaneous sensitivity test of the following 1) cold 2) warmth 3) contact and pain and 4) touch and pressure. The cutaneous sensitivity tests were done in different skin locations. The results showed that between the cold and warmth cutaneous sensitivity tests, the strong and intense spots for the cutaneous sensitivity test for warmth on different skin locations appeared more numerous than the cutaneous sensitivity test for cold. On the other hand between the contact and pain, and touch cutaneous sensitivity test, the strong and intense spots for the cutaneous sensitivity test for contact and pain on different skin locations appeared more numerous than the cutaneous sensitivity for touch and pressure. The experiment therefore conclude that the various stimuli and receptors were also responsible for the various spots and points of adaptation based on different cutaneous sensitivities.
Laboratory Report Experiment No.1 SIMPLE REACTION TIME.;Laboratory Report Experiment No.2 EXTRA SENSORY PHENOMENA.;Laboratory Report Experiment No.3 OPERANT CONDITIONING.;Laboratory Report Experiment No.4 FORMATION OF WORD ASSOCIATION AND PERCEPTUAL DEFENSE.;Laboratory Report Experiment No.5 CREATIVITY.;Laboratory Report Experiment No.6 EXPERIMENTATION ON CUTANEOUS SENSITIVITY.;Laboratory Report Experiment No.7 VERBAL APPEAL AND BODY LANGUAGE.;Laboratory Report Experiment No.8 EMOTIONAL SENSITIVITY.;Laboratory Report Experiment No.9 CONFORMITY.;Laboratory Report Experiment No.10 COLOR STROOP EFFECT.
Laboratory Report:(B.S.Psychology)- Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2